Performance of Different Standard Carnation (Dianthus caryophyllus L.) Cultivars in the Plains of West Bengal, India - Maitra, S.; Roychowdhury, N. (International Journal of Bio-resource and Stress Management, 2013)
The suitability to ten standard carnation cultivars (Dark Red, Yellow with Red, Bright Red, Pink, C. Rimo, Decio, Orange Isac, Lilac Tarres, Tashman Pink and Orange Triumph) in the plains of West Bengal was studied in this experiment. Results revealed that the longest plant producing cultivar was Dark Red (78.36 cm) and the shortest plant producing cultivar was Decio (51.96 cm). Highest leaf producing cultivar was Bright Red (28.96 leaves shoot-1). Cv. Pink produced lowest number of leaves shoot-1 (20.59). Cv. Yellow with Red was identified the longest leaf producer (12.31 cm) and cv. Orange Triumph was identified the shortest (9.18 cm). Widest leaves (0.79 cm) produced by Orange Isac and narrowest leaves were the character of cv. Pink. (0.50 cm). Decio produced the highest number of side-shoots (2.61) and Pink and Orange Isac produced the lowest number of side-shoots (1.08) plant-1. Earliest Flower Bud Initiation (FBI) was recorded with Lilac Tarres (69.66 days) and Orange Isac reached the FBI stage last of all (104.68 days). Bright Red recorded the lowest time period for flower bud development (18.94 days) and Orange Isac recorded the highest time period (24.98 days). In-situ longevity of flowers was found highest with Bright Red (11.78 days) and lowest with Orange Triumph (9.17 days). Bud length and bud diameter though non-significant was found highest with Tashman Pink (3.81 cm) and Lilac Tarres (1.88 cm) respectively. Longest stalks recorded with Dark Red (71.62 cm) and shortest with C. Rimo (49.70 cm). Bright Red was found to produce flowers of highest diameter (7.21 cm) and Tashman Pink was found the lowest flower diameter producing variety (5.85 cm). Variety Dark Red produced highest number of flowers plant-1 (4.54) and Bright Red produced lowest number of flowers plant-1 (2.65). The post-harvest longevity of cut flowers was found maximum with Dark Red (6.27 days) and minimum with Orange Triumph (4.97 days).